A Phased Framework Proposal for the Long-Term Institutionalization of Artificial Intelligence Weapon Systems - Ji-Hee Nam; Hun-Yeong Kwon (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
A Phased Framework Proposal for the Long-Term Institutionalization of Artificial Intelligence Weapon Systems